Analisis Kontribusi dan Pertumbuhan Retribusi Parkir Dalam Upaya Meningkatkan Pendapatan Asli Daerah - Clara Mailoa; Arthur R. Tanihatu; Jansen R. Patty (Journal of Business Application, 2025)
Local governments should dig as much as possible the source of the regional levy, one of the sources is the parking levy. The purpose of this study is to determine (1) The growth of parking levy receipts from 2017 to 2021, (2) The amount of contribution of parking levy receipts to PAD from 2017 to 2021. This type of research is a quantitative research. Data are obtained by conducting documentation and literature. The data analysis technique carried out is calculation of growth and contribution. The results of the data analysis showed that (1) The growth of parking levy receipts in Ambon City in 2017 was 25.22%; in 2018 it was 111.45%; this means that the growth is positive while in 2019 and 2020 the growth is negative, namely only (0.09%) and (40.01%) and in 2021 the growth returned positively by 132.53%. (2) The contribution of parking levy receipts to Local Revenue was 1.42% in 2017; 2.21% in 2018; 2.31% in 2019; in 2020 there was a decrease of 0.61% to 1.70%; and in 2021 it increased by 1.17% to 2.87%.